Nanometer spherical low-temperature rare-earth-based denitration and carbon monoxide removal catalyst as well as preparation method and application thereof
By using nanospherical low-temperature rare earth-based catalysts in the treatment of low-temperature flue gas in the non-electric industry, the problems of insufficient low-temperature activity of existing catalysts and limited synergistic removal capabilities of multiple pollutants have been solved, and efficient low-temperature denitrification and carbon monoxide effects have been achieved.
Patent Information
- Application Number
- CN202510080103.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-19
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-19
AI Technical Summary
The existing low-temperature flue gas denitrition and carbon monoxide catalysts in the non-electric industry have problems such as insufficient low-temperature activity, weak anti-toxicity ability, poor working conditions adaptability and limited synergistic removal ability of multiple pollutants.
Nanosphere low-temperature rare earth-based catalyst is used, and the composite oxide of manganese dioxide and ceria is used as the active component, and iron oxide is used as the cocatalyst. It is prepared by high-temperature hydrothermal-incomplete reverse phase emulsion polymerization-impregnation support method to ensure uniform growth of the active component and sufficient contact with the reaction gas.
It significantly improves the low-temperature denitrification and decarbonization of the catalyst, enhances the ability to resist ammonium sulfide and alkali metal poisoning, and improves the coordinated removal performance of NOx and CO., and has simple process and low cost, which has strong application promotion value.
Smart Images

Figure CN119869546A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a nano-spherical low-temperature rare earth-based denitration and decarbon monoxide catalyst, belonging to the field of industrial flue gas purification. Background Art
[0002] In non-electricity industries, including steel sintering industry, chemical industry, etc., the NO in flue gas x The concentrations of CO and CO are high, which requires catalysts under low temperature conditions to effectively achieve their combined removal. However, catalysts in this field generally face common problems in performance and stability, including insufficient low-temperature activity, weak anti-poisoning ability, poor adaptability to working conditions, and limited ability to synergistically remove multiple pollutants, which affects the efficiency and stability of the catalyst in practical applications.
[0003] With the increasing environmental protection requirements, flue gas treatment technologies in non-power industries are facing higher innovation and application challenges, especially in low-temperature denitrification and decarbon monoxide technologies. Existing catalysts cannot fully meet these requirements, so it is particularly important to develop new catalysts to meet these challenges. Rare earth-based catalysts are regarded as an important direction for the development of denitrification catalysts in the future because of their non-toxicity, low cost and good low-temperature activity. In SCR denitrification technology, flue gas treatment in non-power industries also needs to deal with the challenges of high concentrations of SO2, alkali metals, alkaline earth metals and volatile organic compounds, which have a significant effect on catalyst performance. Therefore, it is necessary to improve the low-temperature activity, resistance to ammonium sulfate poisoning and resistance to alkali metal poisoning of the catalyst, and enhance the resistance to NO x The synergistic removal performance of NO and CO has become a key goal for the future development of SCR catalysts. Considering the technical difficulty and high investment cost of flue gas treatment in the non-power industry, the development of low-temperature catalysts that can simultaneously remove NO and CO has become an important research direction in this field. Summary of the invention
[0004] The purpose of the present invention is to propose a preparation method and application of a nano-spherical low-temperature rare earth-based denitrification and decarbon monoxide catalyst in view of the current situation and existing problems of insufficient catalytic activity of low-temperature denitrification and decarbon monoxide catalysts in flue gas of non-electricity industries.
[0005] A nano-spherical low-temperature rare earth-based denitration and carbon monoxide removal catalyst, characterized in that: the catalyst uses aluminum oxide as a carrier, a composite oxide of manganese dioxide and cerium dioxide as an active component, iron oxide as a co-catalyst, ammonia water as a pH control agent, p-hydroxybenzoic acid as a morphology control agent, polyacrylamide as a template agent, and is prepared by a high-temperature hydrothermal-incomplete inverse emulsion polymerization-impregnation loading method; wherein, based on the mass of the carrier, the mass percentage of the active component is 5-10%, the mass percentage of the co-catalyst is 5-10%, and the mass ratio of manganese dioxide to cerium dioxide in the active component is 1: (0.5-2). The preparation method of the catalyst is as follows:
[0006] (1) Preparation of alumina nanosphere carrier by high temperature hydrothermal method
[0007] Aluminum salt, ammonia water, p-hydroxybenzoic acid, deionized water and ethanol are mixed evenly, and then placed in a hydrothermal reactor for high-temperature hydrothermal reaction. After the reaction is completed, the aluminum oxide nanosphere carrier is obtained by filtering and drying.
[0008] (2) Growth of polyacrylamide by incomplete inverse emulsion polymerization
[0009] The monomer acrylamide, initiator, buffer solution and the alumina nanosphere carrier prepared in step (1) are uniformly mixed to obtain an aqueous phase and continuously stirred, and then n-hexane and an emulsifier are uniformly mixed to obtain an oil phase, and then the oil phase is added dropwise to the aqueous phase and continuously stirred to form an inverse emulsion, and then the inverse emulsion is first placed in an oil bath pot for oil bath reaction and then placed in an ice bath pot for low temperature reaction, then placed in an oil bath pot for oil bath reaction and then placed in an ice bath pot for low temperature reaction, and finally washed three times with deionized water and ethanol to obtain the alumina nanosphere carrier grown with polyacrylamide;
[0010] (3) Growth of active components and promoters by impregnation loading method
[0011] Manganese salt, cerium salt, iron salt and deionized water are mixed evenly to obtain a composite precursor solution, and then the aluminum oxide nanosphere carrier of the polyacrylamide grown obtained in step (2) is placed in the composite precursor solution, and then the mixed solution is placed in an oven for drying, and finally placed in a muffle furnace for calcination to obtain a nano-spherical low-temperature rare earth-based denitrification and decarbon monoxide catalyst.
[0012] In the technical scheme of the present invention: the aluminum salt described in step (1) is aluminum nitrate or aluminum chloride, the ammonia water is an ammonia solution with a mass fraction of 15-20%, and the mass ratio of the aluminum salt, ammonia water, p-hydroxybenzoic acid, deionized water, and ethanol is 1: (3-5): (0.1-0.2): (30-60): (40-80).
[0013] In the technical solution of the present invention: the temperature of the high-temperature hydrothermal reaction described in step (1) is 160-180° C., the time of the high-temperature hydrothermal reaction is 3-6 hours, the drying temperature is 80-100° C., and the drying time is 6-12 hours.
[0014] In the technical solution of the present invention: the initiator described in step (2) is ammonium persulfate, the buffer solution is a sodium phosphate solution with a mass fraction of 10-20%, the mass ratio of acrylamide monomer, initiator, buffer solution, and alumina nanosphere carrier is 1: (0.01-0.03): (10-20): (20-30), and the continuous stirring rate is 100-200 r / min.
[0015] In the technical scheme of the present invention: the emulsifier described in step (2) is a fatty alcohol, the mass ratio of acrylamide monomer, n-hexane and emulsifier is 1: (20-40): (0.05-0.10), the temperature of the oil bath reaction is 50-70° C., the time of the oil bath reaction is 20-30 minutes, and the time of the low-temperature reaction in the ice bath pot is 30-60 minutes.
[0016] In the technical scheme of the present invention: the manganese salt described in step (3) is manganese chloride or manganese nitrate hexahydrate, the cerium salt is cerium chloride or cerium nitrate hexahydrate, the iron salt is ferric chloride hexahydrate or ferric nitrate nonahydrate, and the mass ratio of manganese salt to deionized water is 1: (30-50).
[0017] The technical solution of the present invention is characterized in that: the drying temperature in step (3) is 80-100° C., the drying time is 6-12 hours, the roasting temperature is 500-600° C., and the roasting time is 3-6 hours.
[0018] In the technical solution of the present invention, the above-mentioned catalyst preparation method is applied to the denitrification and carbon monoxide removal under low-temperature flue gas conditions in non-electricity industries.
[0019] The experimental conditions for evaluating the activity of the catalyst of the present invention are as follows: 1 mL of a 20-40 mesh catalyst is taken, poured into a quartz tube with an inner diameter of 6 mm, fixed with quartz wool and wire mesh, and the quartz tube is placed in a tubular furnace, and the actual temperature of the catalytic reaction is adjusted by controlling the heating temperature of the tubular furnace. Intake gas components: NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), CO (1000 ppm), and the rest are N2, the total gas flow rate is 500 mL / min, the temperature is controlled at 90-210°C, and the temperature is kept stable for 30 minutes at every 30°C. The concentrations of NO and CO are measured using a Laoying 3021 portable carbon emission monitor, and the catalyst denitration and carbon monoxide removal efficiency in the temperature range of 150-210°C is higher than 90%.
[0020] Beneficial effects:
[0021] (1) In the present invention, p-hydroxybenzoic acid is used as a morphology control agent to form uniform nanospheres of alumina. In order to enable the active components to grow uniformly on the carrier surface and to fully contact the reaction gas molecules, polyacrylamide is grown on the surface of the alumina nanospheres by an incomplete inverse emulsion polymerization method. Then, the steric effect is used to grow the active components and the co-catalyst components on the surface of the alumina nanospheres while ensuring that they do not agglomerate on the surface of the alumina nanospheres. Finally, the active components and the co-catalyst components are grown on the surface of the alumina nanospheres similar to needle and thread winding. In this way, the active components and the co-catalyst components can be fully exposed, so that they can contact the reaction molecules to the greatest extent possible, thereby improving their low-temperature denitrification activity and low-temperature decarbon monoxide activity.
[0022] (2) Conventional inverse emulsion polymerization causes polyacrylamide to grow uniformly on the surface of the alumina support without forming a steric hindrance effect. Therefore, it is necessary to place it in an ice bath during the reaction process to lower the reaction temperature and slow down the reaction rate. This cycle causes the polyacrylamide to not completely cover the alumina surface, leaving space for the growth of active components and co-catalyst components.
[0023] (3) The active components and the co-catalyst components are impregnated and loaded on the surface of the alumina nanospheres and in the space of the polyacrylamide by utilizing the steric hindrance effect, and the polyacrylamide is removed by high-temperature calcination. This can not only convert the precursor into an oxide, but also utilize the reducing atmosphere formed by the polyacrylamide during the calcination process to increase the oxygen vacancy concentration on the catalyst surface, thereby further improving the low-temperature catalytic activity;
[0024] (4) In the present invention, alumina is used as a carrier, manganese oxide and cerium oxide are used as active components, and iron oxide is used as a co-catalyst, so that the catalyst has the mechanical strength and surface acidity of alumina, the excellent redox performance and oxygen storage and release performance of manganese oxide and cerium oxide, and also has rich acid sites of iron oxide, thereby ensuring its low-temperature denitrification and decarbon monoxide performance.
[0025] Therefore, the catalyst prepared by the present invention not only has excellent low-temperature flue gas denitrification and carbon monoxide removal performance, but also the catalyst component is environmentally friendly, has a simple preparation process, low cost, high cost performance, and has strong application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 TEM image of the carrier prepared in Example 1;
[0027] Figure 2 TEM image of the catalyst prepared in Example 1;
[0028] Figure 3 The NO removal performance diagram of the catalysts prepared in Examples 1-3 and Comparative Examples 1-2;
[0029] Figure 4 This is a graph showing the CO removal performance of the catalysts prepared in Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with examples. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following examples.
[0031] Example 1
[0032] (1) Preparation of alumina nanosphere carrier by high temperature hydrothermal method
[0033] Weigh 20.000g of aluminum nitrate, 60.000g of 15% ammonia solution, 2.000g of p-hydroxybenzoic acid, 600.000g of deionized water and 800.000g of ethanol, mix and stir evenly, then place in a hydrothermal reactor for hydrothermal reaction at 160°C for 3h. After the reaction is completed, filter and place in an oven for drying at 80°C for 6h to obtain an alumina nanosphere carrier (TEM image of the carrier is as shown in FIG. Figure 1 shown);
[0034] (2) Growth of polyacrylamide by incomplete inverse emulsion polymerization
[0035] 0.479 g of monomer acrylamide, 0.005 g of ammonium persulfate, 4.787 g of 10% sodium phosphate solution and 9.574 g of the alumina nanosphere carrier prepared in step (1) were weighed, mixed and placed in an open beaker, and then the mixed solution was continuously stirred at a stirring rate of 100 r / min at room temperature to obtain an aqueous phase, 9.580 g of n-hexane and 0.024 g of fatty alcohol were weighed, placed in a beaker and mixed to obtain an oil phase, and the oil phase was dripped dropwise into the continuously stirred aqueous phase to obtain an inverse emulsion phase solution, the inverse emulsion phase solution was first placed in a 50° C. oil bath to react for 20 min, and then placed in an ice bath to react for 30 min, and then placed in a 50° C. oil bath to react for 20 min, and then placed in an ice bath to react for 30 min, and after the reaction, it was washed three times with deionized water and ethanol to obtain an alumina nanosphere carrier grown with polyacrylamide;
[0036] (3) Growth of active components and promoters by impregnation loading method
[0037] 0.485 g of manganese chloride, 0.240 g of cerium chloride, 0.851 g of ferric chloride hexahydrate and 25.542 g of deionized water were weighed and mixed to obtain a precursor solution. Then, the alumina nanosphere carrier of the polyacrylamide grown in step (2) was mixed and impregnated with the precursor solution obtained in step (3), and placed in an oven for drying at 80° C. for 6 h. After drying, the catalyst was calcined at 500° C. for 3 h to obtain a catalyst (based on the mass of the carrier, the mass percentage of the active component was 5%, the mass percentage of the co-catalyst was 5%, the mass ratio of manganese dioxide to cerium dioxide in the active component was 1:0.5, and the TEM image of the catalyst was as follows: Figure 2 shown);
[0038] (4) Catalytic activity test
[0039] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), CO (1000ppm) and the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-210℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO and CO concentrations, and the catalyst denitrification and carbon monoxide removal efficiency is higher than 90% in the temperature range of 150-210℃.
[0040] Example 2
[0041] (1) Preparation of alumina nanosphere carrier by high temperature hydrothermal method
[0042] Weigh 20.000g of aluminum nitrate, 100.000g of 20% ammonia solution, 4.000g of p-hydroxybenzoic acid, 1200.000g of deionized water and 1600.000g of ethanol, mix and stir evenly, then place in a hydrothermal reactor for hydrothermal reaction at 180°C for 6h, filter after the reaction and place in an oven for drying at 100°C for 12h to obtain an alumina nanosphere carrier;
[0043] (2) Growth of polyacrylamide by incomplete inverse emulsion polymerization
[0044] 0.319 g of acrylamide monomer, 0.010 g of ammonium persulfate, 6.383 g of 20% sodium phosphate solution and 9.574 g of the alumina nanosphere carrier prepared in step (1) were weighed, mixed and placed in an open beaker, and then the mixed solution was continuously stirred at a stirring rate of 200 r / min at room temperature to obtain an aqueous phase, 12.765 g of n-hexane and 0.032 g of fatty alcohol were weighed, placed in a beaker and mixed to obtain an oil phase, and the oil phase was dripped dropwise into the continuously stirred aqueous phase to obtain an inverse emulsion phase solution, the inverse emulsion phase solution was first placed in a 70° C. oil bath to react for 30 min, and then placed in an ice bath to react for 60 min, and then placed in a 70° C. oil bath to react for 30 min, and then placed in an ice bath to react for 60 min, and after the reaction, it was washed three times with deionized water and ethanol to obtain an alumina nanosphere carrier growing polyacrylamide;
[0045] (3) Growth of active components and promoters by impregnation loading method
[0046] Weigh 1.089 g of manganese nitrate hexahydrate, 1.664 g of cerium nitrate hexahydrate, 2.503 g of ferric chloride hexahydrate and 125.141 g of deionized water, mix them evenly to obtain a precursor solution, then mix and impregnate the alumina nanosphere carrier of polyacrylamide grown in step (2) with the precursor solution obtained in step (3), place them in an oven and dry them at 1000° C. for 12 h, and after drying, calcine them at 600° C. for 6 h to obtain a catalyst (based on the mass of the carrier, the mass percentage of the active component is 10%, the mass percentage of the co-catalyst is 10%, and the mass ratio of manganese dioxide to cerium dioxide in the active component is 1:2);
[0047] (4) Catalytic activity test
[0048] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), CO (1000ppm) and the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-210℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO and CO concentrations, and the catalyst denitrification and carbon monoxide removal efficiency is higher than 90% in the temperature range of 150-210℃.
[0049] Example 3
[0050] (1) Preparation of alumina nanosphere carrier by high temperature hydrothermal method
[0051] Weigh 20.000g of aluminum nitrate, 80.000g of 18% ammonia solution, 3.000g of p-hydroxybenzoic acid, 900.000g of deionized water and 1200.000g of ethanol, mix and stir evenly, then place in a hydrothermal reactor for hydrothermal reaction at 170°C for 5h, filter after the reaction and place in an oven for drying at 90°C for 10h to obtain an alumina nanosphere carrier;
[0052] (2) Growth of polyacrylamide by incomplete inverse emulsion polymerization
[0053] 0.383 g of acrylamide monomer, 0.008 g of ammonium persulfate, 5.745 g of 15% sodium phosphate solution and 9.574 g of the alumina nanosphere carrier prepared in step (1) were weighed, mixed and placed in an open beaker, and then the mixed solution was continuously stirred at a stirring rate of 180 r / min at room temperature to obtain an aqueous phase, 11.495 g of n-hexane and 0.031 g of fatty alcohol were weighed, placed in a beaker and mixed to obtain an oil phase, and the oil phase was dripped dropwise into the continuously stirred aqueous phase to obtain an inverse emulsion phase solution, the inverse emulsion phase solution was first placed in a 60° C. oil bath to react for 20 min, and then placed in an ice bath to react for 40 min, and then placed in a 60° C. oil bath to react for 20 min, and then placed in an ice bath to react for 40 min, and after the reaction, it was washed three times with deionized water and ethanol to obtain an alumina nanosphere carrier growing polyacrylamide;
[0054] (3) Growth of active components and promoters by impregnation loading method
[0055] Weigh 0.576g of manganese chloride, 0.570g of cerium chloride, 1.012g of ferric chloride hexahydrate and 40.478g of deionized water and mix them evenly to obtain a precursor solution. Then, the aluminum oxide nanosphere carrier of the polyacrylamide grown prepared in step (2) is mixed and impregnated with the precursor solution prepared in step (3), and placed in an oven to dry at 90°C for 10h. After drying, the catalyst is calcined at 550°C for 5h to obtain a catalyst (based on the mass of the carrier, the mass percentage of the active component is 8%, the mass percentage of the co-catalyst is 6%, and the mass ratio of manganese dioxide to cerium dioxide in the active component is 1:1);
[0056] (4) Catalytic activity test
[0057] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), CO (1000ppm) and the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-210℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO and CO concentrations, and the catalyst denitrification and carbon monoxide removal efficiency is higher than 90% in the temperature range of 150-210℃.
[0058] Comparative Example 1
[0059] (1) Preparation of carrier
[0060] Except that p-hydroxybenzoic acid is not used as a morphology control agent during the preparation of the catalyst, other conditions are the same as those in Example 1;
[0061] (2) Catalytic activity test
[0062] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tubular furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tubular furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), CO (1000ppm), and the rest are N2. The total gas flow rate is 500mL / min, and the temperature is controlled at 90-210℃. Stay stable for 30min every 30℃. Use Laoying 3021 portable carbon emission monitor to measure NO and CO concentrations. The catalyst denitrification efficiency at 150℃ is 35.6%, and the carbon monoxide removal efficiency is 52.7%;
[0063] (3) Contrast effect
[0064] Compared with Example 1, p-hydroxybenzoic acid was used as a morphology control agent during catalyst preparation, and the prepared catalyst was irregular nanoparticles, resulting in a reduced proportion of exposed active sites, thereby reducing the low-temperature catalytic activity.
[0065] Comparative Example 2
[0066] (1) Preparation of catalyst
[0067] Except that the catalyst was not placed in an ice bath to lower the reaction temperature and slow down the reaction rate during preparation, other conditions were the same as in Example 2;
[0068] (2) Catalytic activity test
[0069] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tubular furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tubular furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), CO (1000ppm), and the rest are N2. The total gas flow rate is 500mL / min, and the temperature is controlled at 90-210℃. Stay stable for 30min every 30℃. Use Laoying 3021 portable carbon emission monitor to measure NO and CO concentrations. The catalyst denitrification efficiency at 150℃ is 53.3%, and the carbon monoxide removal efficiency is 63.1%;
[0070] (3) Contrast effect
[0071] Compared with Example 2, the catalyst is placed in an ice bath during preparation to lower the reaction temperature and slow down the reaction rate, resulting in uniform growth of polyacrylamide on the surface of the alumina carrier without forming a steric hindrance effect. The space reserved for the growth of active components and co-catalyst components is not as good as in Example 2, and the synaptic structure of the prepared catalyst may be lower, resulting in reduced denitrification and decarbon monoxide activity.
Claims
1. A nano-spherical low-temperature rare earth-based denitrification and carbon monoxide removal catalyst, characterized in that: The catalyst uses aluminum oxide as a carrier, a composite oxide of manganese dioxide and cerium dioxide as an active component, iron oxide as a co-catalyst, ammonia water as a pH control agent, p-hydroxybenzoic acid as a morphology control agent, and polyacrylamide as a template agent, and is prepared by a high-temperature hydrothermal-incomplete inverse emulsion polymerization-impregnation loading method; wherein, based on the mass of the carrier, the mass percentage of the active component is 5-10%, the mass percentage of the co-catalyst is 5-10%, and the mass ratio of manganese dioxide to cerium dioxide in the active component is 1:(0.5-2).
2. A method for preparing the catalyst according to claim 1, characterized in that: The preparation method of the catalyst is as follows: (1) Preparation of alumina nanosphere carrier by high temperature hydrothermal method Aluminum salt, ammonia water, p-hydroxybenzoic acid, deionized water and ethanol are mixed evenly, and then placed in a hydrothermal reactor for hydrothermal reaction, and after the reaction is completed, filtered and dried to obtain an alumina nanosphere carrier; (2) Growth of polyacrylamide by incomplete inverse emulsion polymerization The monomer acrylamide, the initiator, the buffer solution, and the alumina nanosphere carrier prepared in step (1) are uniformly mixed to obtain an aqueous phase and continuously stirred, and then n-hexane and an emulsifier are uniformly mixed to obtain an oil phase, and then the oil phase is added dropwise to the aqueous phase and continuously stirred to form an inverse emulsion, and then the inverse emulsion is first placed in an oil bath pot for oil bath reaction and then placed in an ice bath pot for low temperature reaction, and finally washed three times with deionized water and ethanol to obtain the alumina nanosphere carrier grown with polyacrylamide; (3) Growth of active components and promoters by impregnation loading method Manganese salt, cerium salt, iron salt and deionized water are mixed evenly to obtain a composite precursor solution, and then the aluminum oxide nanosphere carrier of the polyacrylamide grown obtained in step (2) is placed in the composite precursor solution, and then the mixed solution is placed in an oven for drying, and finally placed in a muffle furnace for calcination to obtain a nano-spherical low-temperature rare earth-based denitrification and decarbon monoxide catalyst.
3. The preparation method according to claim 2, characterized in that: The aluminum salt described in step (1) is aluminum nitrate or aluminum chloride, the mass fraction of ammonia water is 15-20%, and the mass ratio of aluminum salt, ammonia water and p-hydroxybenzoic acid is 1: (3-5): (0.1-0.2).
4. The preparation method according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step (1) is 160-180° C., and the time of the hydrothermal reaction is 3-6 hours; the temperature of the drying is 80-100° C., and the time of the drying is 6-12 hours.
5. The preparation method according to claim 2, characterized in that: The initiator described in step (2) is ammonium persulfate, the buffer solution is a sodium phosphate solution with a mass fraction of 10-20%, and the mass ratio of acrylamide monomer, initiator, buffer solution, and alumina nanosphere carrier is 1: (0.01-0.03): (10-20): (20-30).
6. The preparation method according to claim 2, characterized in that: The emulsifier described in step (2) is a fatty alcohol, the mass ratio of monomer acrylamide, n-hexane and emulsifier is 1: (20-40): (0.05-0.10), the temperature of the oil bath reaction is 50-70° C., the time of the oil bath reaction is 20-30 minutes, and the time of the low-temperature reaction in the ice bath pot is 30-60 minutes.
7. The preparation method according to claim 2, characterized in that: The manganese salt described in step (3) is manganese chloride or manganese nitrate hexahydrate, the cerium salt is cerium chloride or cerium nitrate hexahydrate, and the iron salt is ferric chloride hexahydrate or ferric nitrate nonahydrate.
8. The preparation method according to claim 1, characterized in that: The drying temperature in step (3) is 80-100° C., and the drying time is 6-12 hours; the roasting temperature is 500-600° C., and the roasting time is 3-6 hours.
9. Application of the catalyst according to claim 1 in denitration and removal of carbon monoxide in low-temperature flue gas conditions in non-power industries.
10. The use according to claim 9, characterized in that: Non-electric industries specifically refer to the steel sintering industry and the chemical industry.
Citation Information
Patent Citations
Electrode material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery electrode and non-aqueous electrolyte secondary battery using same
CN105637685A
Catalyst for FCC gasoline sweetening and preparation method thereof
CN107096552A
Two-stage catalyst for removing NOx and VOCs (Volatile Organic Compounds) through concerted catalysis and preparation method of two-stage catalyst
CN116850986A
Spindle-like or spherical alkali aluminum sulfate hydroxide, its production and compounding agent for resin
JP2000007326A
Positive electrode for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery arranged by use thereof
JP2015118801A